Advancing healthcare through mobile collaboration: a survey of intelligent nursing robots research - Wang, Boyuan; Chen, Shanji; Xiao, Gexin (Frontiers in Public Health, 2024)
Mobile collaborative intelligent nursing robots have gained significant attention in the healthcare sector as an innovative solution to address the challenges posed by the increasing aging population and limited medical resources. This article provides a comprehensive overview of the research advancements in this field, covering hospital care, home older adults care, and rehabilitation assistance. In hospital settings, these robots assist healthcare professionals in tasks such as patient monitoring, medication management, and bedside care. For home older adults care, they enhance the older adults sense of security and quality of life by offering daily life support and monitoring. In rehabilitation, these robots provide services such as physical rehabilitation training and social interaction to facilitate patient recovery. However, the development of intelligent nursing robots faces challenges in technology, ethics, law, and user acceptance. Future efforts should focus on improving robots’ perceptual and cognitive abilities, enhancing human-robot interaction, and conducting extensive clinical experiments for broader applications.